Competition, strategy, management accounting information and firm performance: evidence from Vietnamese small and medium enterprises - Lê Mộng Huyền; Đỗ Huyền Trang; Trần Thị Quanh (My University, 2019)
Competition, strategy, management accounting information and firm performance: evidence from Vietnamese small and medium enterprises
Keywords: Competition; Management accounting; SMEs performance